PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PENERAPAN MODELPROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA GAME DIGITAL BERBASIS CANVA PADA PEMBELAJARAN IPA DI KELAS V SEKOLAH DASAR - Oliver Chelsea Sitanggang; Wiwik Kurniati; Natasya T (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the increase in student learning motivation through the application of the Problem Based Learning (PBL) Model assisted by Canva based digital game media in science learning in grade V of elementary school. This study is a classroom action research that uses qualitative and quantitative approaches. The subjects of this study were teachers and 28 grade V students. The study was conducted in one cycle, consisting of planning, implementation, observation, and reflection. Data were collected through observation and questionnaire instruments. Based on the results of the research that has been done, the application of the Problem Based Learning (PBL) model assisted by Canva based digital game media has been proven to increase student learning motivation, seen from the increase in the average student learning motivation from 35.7% in the pre-cycle stage with a low category to 73% in the first cycle with a high category. And students become more active, enthusiastic, brave in discussing, and more enthusiastic in participating in learning. It can be concluded that the application of the PBL model assisted by Canva based digital game media is effective in increasing student learning motivation in science learning.